Judd Ofelt Analysis and Optical Properties of Eu\(^{3 + }\) Doped Tellurite Glasses - Hong, Tran Thi; Dung, Phan Tien; Quang, Vu Xuan (Communications in Physics, 2014)
In this work, the structural characteristic and photoluminescence properties of Eu\(^{3 + }\) doped B\(_{2}\)O\(_{3}\)-TeO\(_{2}\) -ZnO-Na\(_{2}\)O glasses were investigated. These glasses were prepared by a melting method in air, combined with thermal annealing at 350\(^{°}\)C, 450\(^{°}\)C and 550\(^{°}\)C for different duration times. The structural analysis results of these glasses revealed the formation of micro-crystals in the annealed host glass. The photoluminescence spectra of Eu\(^{3 + }\) doped in these samples were observed. The local vibration mode around Eu\(^{3 + }\) ions was investigated by the phonon side-band (PSB) associated with \(^{7}\!F_{0}-^{5}D_{2}\) transition of Eu\(^{3+}\). Judd-Ofelt parameters were then evaluated based on photoluminescence spectra and the luminescence intensity ratios of \(^{5}D_{0} → ^{7}\!F_{J}\) (\(J=2, 4\) and 6) to \(^{5}D_{0} → ^{7}\!F_{1}\) transition were predicted. The obtained results were then used to calculate \(Ω _{2},\;Ω _{4},\; Ω _{6} \) parameters based on Judd-Ofelt theory. These \(Ω _{2}\), \(Ω _{4}\), \(Ω _{6}\) parameters allow to derive radiative properties of Eu\(^{3 + }\) ions in glass material such as transition probabilities, radiative lifetimes and peak stimulated emission cross-section for the \(^{5}D_{0} → ^{7}\!F_{J}\) transitions.